Geometric and engineering drawing - Morling, K. (London : Routledge, Taylor & Francis Group, 2010)
"This introduction to descriptive geometry and drafting guides the student to create professional 2D and 3D working drawings that comply with the latest ISO standards of technical product specifications. This heavily updated new edition with extensive new coverage now applies to CAD as well as conventional drawing"--
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Mechanical drawing